Efektifitas Model Guided Discovery Learning Terhadap Kemampuan Pemecahan Masalah Materi Bangun Ruang Kelas V - Anugrah Nur Pratiwi; Mira Azizah; Kartinah Kartinah (Jurnal Kualita Pendidikan, 2023)
The background of this research is students who experience difficulties in solving mathematical problems, students who have not mastered the basic concepts of geometric shapes, learning models have not been able to stimulate students in solving mathematical problems. The research objective was to determine the effectiveness of the guided discovery learning model on the ability to solve geometric material problems. This research is an experimental research with a True-Experimental design and uses a pretest-posttest control group design. The sample in this study were fifth grade students consisting of two classes, each consisting of 24 students. The results of this study show the calculation of the average increase in the experimental class and control class, reinforced by the results of the t-test obtaining a significance value of 0.03. Where the significance value is less than 0.05 (0.03 <0.05) then H0 is rejected. So that the guided discovery learning learning model is better than the problem solving abilities of students who take part in conventional learning. Mastery learning in the experimental class with a classical score percentage of 92% and 79% classical value in the control class, so that the guided discovery learning model is said to be effective in improving problem solving abilities.